Crystallization and preliminary X-ray diffraction analysis of a Lys49-PLA 2 homologue from Cerrophidion Godmani venom - De Azevedo, W. F. [UNESP]; Ward, R. J. [UNESP]; Gutiérrez, J. M.; Diaz-Oreiro, C. [UNESP]; Arni, R. K. [UNESP] (My University, 1998)
Lys49-Phospholipase A 2 (Lys49-PLA 2) homologues damage membranes by a Ca 2+-independent mechanism which does not involve catalytic activity. The myotoxic Lys-49 phospholipase myotoxin II from Cerrophidion (Bothrops) godmani has been crystallized, and X-ray diffraction data were collected to 2.8 Å resolution. Preliminary analysis reveals the presence of one molecule in the asymmetric unit.